Evaluation of fungicides and biocontrol agents for suppression of banded leaf and sheath blight of maize (Zea mays) - S.I. HARLAPUR, L.S. RAJPUT* and (Indian Phytopathology, 2015)
Field experiment was conducted during kharif season to assess the possibility of managing leaf and sheath blight of maize (Zea mays L.) by different combinations of seed dressing fungicides and biocontrol agents along with foliar spray. Seed treatment with Pseudomonas fluorescens (10 g/kg) of seed combined with two sprays of Propiconazole (0.1%) 30 and 40 days after sowing gave maximum grain yield (80.42 q/ha), stover yield (10.75 t/ha) and 100-seed weight (39.51 g) with minimum percentage disease intensity (20.40% on 1-5 scale), followed by seed treatment with Pseudomonas fluorescens (10 g/kg) combined with two sprays of Hexaconazole (0.1%) and seed treatment with Carbendazim (2.5 g/kg) combined with two sprays of Propiconazole @ 0.1% for effective control of BSLB. Seed treatment with Pseudomonas fluorescens (10 g/l) combined with two sprays of Propiconazole (0.1%) 30 and 40 days after sowing resulted in increase in grain yield and stover yield by 40.72 and 44.68%, respectively with highest disease control efficacy (68.90%). Use of biocontrol agents with fungicides was found as best strategy for BSLB management.